Adaptive evolution of a melanized fungus reveals robust augmentation of radiation resistance by abrogating non‐homologous end‐joining. (10th November 2020) - Romsdahl, Jillian; Schultzhaus, Zachary; Chen, Amy; Liu, Jing; Ewing, Alexander; Hervey, Judson; Wang, Zheng
Summary: Fungi have been observed to exhibit resistance to high levels of ionizing radiation despite sharing most DNA repair mechanisms with other eukaryotes. Radioresistance, in fact, is such a common feature in fungi that it is difficult to identify species that exhibit widely different radiosensitivities, which in turn has hampered the identification of genetic elements responsible for this resistance phenotype. Due to the inherent mutagenic properties of radiation exposure, however, this can be addressed through adaptive laboratory evolution for increased ionizing radiation resistance. Here, using the black yeast Exophiala dermatitidis, we demonstrate that resistance to γ‐radiation can be greatly increased through repeated rounds of irradiation and outgrowth. Moreover, we find that the small genome size of fungi situates them as a relatively simple functional genomics platform for identification of mutations associated with ionizing radiation resistance. This enabled the identification of genetic mutations in genes encoding proteins with a broad range of functions from 10 evolved strains. Specifically, we find that greatly increased resistance to γ‐radiation is achieved in E. dermatitidis through disruption of the non‐homologous end‐joining pathway, with three individual evolutionary paths converging to abolish this DNA repair process. This result suggests that non‐homologous end‐joining, even in haploid cells where homologous chromosomes are not present during much of the cell cycle, is an impediment to repair of radiation‐induced lesions in this organism, and that the relative levels of homologous and non‐homologous repair in a given fungal species may play a major role in its radiation resistance.